2016
DOI: 10.12740/app/61610
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the sibling relationship in adulthood. Polish adaptation of STQ-Now

Abstract: SummaryAim: The main aim was to develop a Polish version of the STQ-Now, an American questionnaire created by Stewart and colleagues to evaluate the current sibling relationship. Method:The sample of 416 adults, 18 to 36 years old, completed a survey that consisted of a sociodemographic form, the STQ-Now and one of three questionnaires: the ASRQ, the SWS or the UCLA. Results:The five-factor structure of the STQ-Now was validated using confirmatory factor analysis, however, because of the low level of reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…Lack of agreement in the sibling subsystem may reduce the ability to solve problems in a constructive way and inhibits the creation of proper communication patterns (Walęcka-Matyja, 2018). The obtained results of the research on correlations between the factor of conflict and the psychosocial functioning of adult siblings correspond with the findings obtained by the researchers so far (Capodieci, 2006;Szymańska, 2016).…”
Section: Strona 91supporting
confidence: 90%
See 2 more Smart Citations
“…Lack of agreement in the sibling subsystem may reduce the ability to solve problems in a constructive way and inhibits the creation of proper communication patterns (Walęcka-Matyja, 2018). The obtained results of the research on correlations between the factor of conflict and the psychosocial functioning of adult siblings correspond with the findings obtained by the researchers so far (Capodieci, 2006;Szymańska, 2016).…”
Section: Strona 91supporting
confidence: 90%
“…The way how family members, including siblings, communicate with each other is related to the development of specific types of interpersonal relationships. In the sibling subsystem, there are relationships based on kindness and friendship (Warmth, Mutuality), connected with conflict and hostility (Conflict, Criticism), connected with a struggle for power (Domination), related to competition and jealousy between siblings (Rivalry, Parental Favouritism) as well as relationships showing lack of interest in the siblings (Indifference) (Szymańska, 2016;Walęcka-Matyja, 2016). It should be stressed that the very nature of sibling interpersonal relationships refers to the fact that it is ambivalent.…”
Section: The Problem Matter and The Aim Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing the importance of life satisfaction for human daily functioning, it is crucial to foster and maintain its high level in adulthood, especially the early phase. Studies show that young adults are at special risk of mental disorder (Szafraniec 2011) and need additional support to ease their passage into a new life period. Unfortunately, it appears that they are increasingly subject to discomfort, anxiety and other mental problems during this period: Stallman (2010) reports that more than 80% of students declared elevated levels of distress, nearly one-fifth reported symptoms of serious mental illness, and almost two-thirds reported mild or moderate issues.…”
Section: Life Satisfaction Among Adultsmentioning
confidence: 99%
“…Thirdly, research has showed that in middle/later adulthood and in old-age sibling, ties are characterized by a stabilization of contact between siblings, as well as by an increase in giving/receiving help, and of levels of reciprocal preoccupation and emotional support (e.g., Avioli, 1989; Cicirelli, 1995; Lu, 2007; Szymańska, 2016; Van Volkom, 2006; Van Volkom, Machiz, & Reich, 2011; White, 2001; Whiteman et al, 2011). In particular, there is a general correlation between an increase in social companionship and emotional support and a decrease in instrumental support (e.g., Lu, 2007; Scharf et al, 2005).…”
Section: Sibling Relationships Across the Life Spanmentioning
confidence: 99%